2010
DOI: 10.1074/jbc.m110.125658
|View full text |Cite
|
Sign up to set email alerts
|

Cytohesin-2/ARNO, through Its Interaction with Focal Adhesion Adaptor Protein Paxillin, Regulates Preadipocyte Migration via the Downstream Activation of Arf6

Abstract: The formation of primitive adipose tissue is the initial process in adipose tissue development followed by the migration of preadipocytes into adipocyte clusters. Comparatively little is known about the molecular mechanism controlling preadipocyte migration. Here, we show that cytohesin-2, the guaninenucleotide exchange factor for the Arf family GTP-binding proteins, regulates migration of mouse preadipocyte 3T3-L1 cells through Arf6. SecinH3, a specific inhibitor of the cytohesin family, markedly inhibits mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…ARNO) to the plasma membrane, 41 and cytohesin-2, in turn, interacts with the focal contact protein paxillin. 42 We, therefore, argue that, in the absence of Lmx1b, podocytes contain a stiffer actin cytoskeleton, which may make the podocytes more vulnerable. A similar scenario has been proposed for the mechanism underlying hereditary forms of FSGS caused by mutations in ACTN4.…”
Section: Discussionmentioning
confidence: 99%
“…ARNO) to the plasma membrane, 41 and cytohesin-2, in turn, interacts with the focal contact protein paxillin. 42 We, therefore, argue that, in the absence of Lmx1b, podocytes contain a stiffer actin cytoskeleton, which may make the podocytes more vulnerable. A similar scenario has been proposed for the mechanism underlying hereditary forms of FSGS caused by mutations in ACTN4.…”
Section: Discussionmentioning
confidence: 99%
“…Arl4D plays a role in activating cytohesin-2/ARNO and Arf6, thus acting as a novel regulator of actin reorganization (15,19). Interestingly, cytohesin-2/ARNO and Arf6 control the migration of 3T3-L1 preadipocytes (20). During adipogenesis, adipocytes morphologically change from fibroblastic cells to round, lipid-laden cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences demonstrated that Arf6GEF regulates Arf6 activation and its downstream effectors control activity of various intracellular signal molecules during cell migration ( Figure 1B) (Santy and Casanova 2001, Palacios and D'Souza-Schorey 2003, Torii et al 2010. In particular, it is well known that Arf6GEF cytohesin-1 and cytohesin-2 control cell migration.…”
Section: Switching Arf6 Signal Through Arf6gef and Arf6gap Controls Cmentioning
confidence: 99%
“…For example, cytohesin-associated scaffold protein (CASP)/Cybr/cytohesin-interacting protein (CYTIP) (Mansour et al 2002, Tang et al 2002, Boehm et al 2003, interaction protein for cytohesin exchange factor (IPCEF)/KIAA0403 (Venkateswarlu 2003), RLIP76/RalBP1 (Lee et al 2014), ADP-ribosylation factor-like protein 4D (Arl4D) (Hofmann et al 2007, Li et al 2007), paxillin (Torii et al 2010), actinin-1 and CCDC120 ) are known as cytohesin interacting protein.…”
Section: Cytohesin-2 Binding Proteinsmentioning
confidence: 99%